Human rights and the United Nations - Bapari, Halim (Frónesis)
Human Rights are universal supreme rights which are possessed by all human being irrespective of their race, caste, Nationality. Sex, Language etc. It is provided in the charter that the General Assembly shaIl initiate studies and make recommendations for the purpose of promoting International co-operation in the economic, social, cultural, educational and health flelds and assist in the realisation of the human rights and fundamental freedoms for aH. The United Nations shaIl promote universal respect for and observance of human rights and fundamental freedom for all without distinction as to race, religion, Sex, Language. The United Nations many specialised Agencies directly human rights work in the world of every places. The humam rights occupy a signiflcant place under the character, but it is divided as to whether human rights have become legal rights under the law ofUnited Nations.